Health Care Seeking and Risk Behaviors among High School Students in the Context of a School-Based Health Center - Audardottir-Goulay, Hilda; Mullen, Beka; Greiner, Allen; Hobson, Kenosha; Satterwhite, Catherine L (Kansas Journal of Medicine, 2013)
Background. To address adolescent health needs in urban Wyandotte County, Kansas, a school-based health center (SBHC) was opened in March 2012. Students were surveyed to inform SBHC operations. Methods. All Wyandotte High School students were invited to complete an online survey in class in May 2012. Questions on demographics, health care seeking behaviors, behavioral risk factors, and missed school days were included. Results. Of 1,240 eligible students, 398 responded (32.3%). Nearly half (45.8%) reported that the emergency room or hospital was the location where they usually would seek health care. Females were more likely than males to report less access to mental health counseling (15.1% vs 10.8%, p = 0.01) or reproductive health care (7.7% vs 5.7%, p = 0.03) when needed and were more likely to miss school due to a health problem (54.0% vs 37.9% missed ≥ 1 day in past 4 weeks, p = 0.006). Males were more likely to report having had sex (59.2% vs 46.9%, p = 0.02) while females were more likely to report never using a condom when having sex (30.6% vs 18.3%, p = 0.001). Almost two-thirds (61.9%) of respondents were aware of the SBHC; 18.7% had used the SBHC. Conclusions. Students do not have adequate access to primary care, including sexual and mental health care. Using these data, the SBHC can be better adapted to meet student needs.